Considerations Regarding Theoretical Foundations of Information Infrastructure and Economic Growth - Xiaoliang ZHANG; Jianbo WANG; Iolanda-Petronela GROSU (Revista de Management Comparat International, 2025)
This paper provides an in-depth theoretical analysis of the fundamentals of information infrastructure and its relationship to economic growth and development. The study examines the concept and classification of information infrastructure and the conceptual framework used to understand its role in economic dynamics. Using a qualitative approach based on a critical literature review and recent empirical research, the paper explores the differences and connections between economic growth (as a quantitative process) and economic development, with a focus on the social and qualitative dimensions. The findings highlight the importance of information infrastructure as a key factor in improving productivity, competitiveness and social inclusion. The study concludes that a deeper understanding of these relationships is essential for the development of effective policies that support sustainable economic growth and equitable development. Future research directions are proposed, including exploring the impact of emerging digital infrastructure and regional differences on economic processes.